ANSWER
![x=\frac{13}{62}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B13%7D%7B62%7D)
and
e have
EXPLANATION
![17x-3y=4---(1)](https://tex.z-dn.net/?f=17x-3y%3D4---%281%29)
![2x-4y=1](https://tex.z-dn.net/?f=2x-4y%3D1)
Let us make y the subject and call it equation (2)
![2x=1+4y](https://tex.z-dn.net/?f=2x%3D1%2B4y)
![x=\frac{1}{2}+2y--(2)](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B1%7D%7B2%7D%2B2y--%282%29)
We put equation (2) in to equation (1)
![17(\frac{1}{2}+2y)-3y=4](https://tex.z-dn.net/?f=17%28%5Cfrac%7B1%7D%7B2%7D%2B2y%29-3y%3D4)
![\frac{17}{2}+34y-3y=4](https://tex.z-dn.net/?f=%5Cfrac%7B17%7D%7B2%7D%2B34y-3y%3D4)
![34y-3y=4- \frac{17}{2}](https://tex.z-dn.net/?f=34y-3y%3D4-%20%5Cfrac%7B17%7D%7B2%7D%20)
Simplify to get,
![31y= \frac{8-17}{2}](https://tex.z-dn.net/?f=31y%3D%20%5Cfrac%7B8-17%7D%7B2%7D%20)
![31y= \frac{-9}{2}](https://tex.z-dn.net/?f=31y%3D%20%5Cfrac%7B-9%7D%7B2%7D%20)
Divide both sides by 31,
![y= \frac{-9}{2} \div 31](https://tex.z-dn.net/?f=y%3D%20%5Cfrac%7B-9%7D%7B2%7D%20%5Cdiv%2031)
![y= \frac{-9}{2} \times \frac{1}{31}](https://tex.z-dn.net/?f=y%3D%20%5Cfrac%7B-9%7D%7B2%7D%20%5Ctimes%20%5Cfrac%7B1%7D%7B31%7D)
![y= \frac{-9}{62}](https://tex.z-dn.net/?f=y%3D%20%5Cfrac%7B-9%7D%7B62%7D)
We put this value in to equation (2) to get,
![x=\frac{1}{2}+2\times -\frac{9}{62}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B1%7D%7B2%7D%2B2%5Ctimes%20-%5Cfrac%7B9%7D%7B62%7D)
![x=\frac{1}{2} -\frac{18}{62}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B1%7D%7B2%7D%20-%5Cfrac%7B18%7D%7B62%7D)
We collect LCM to obtain,
![x=\frac{31-18}{62}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B31-18%7D%7B62%7D)
![x=\frac{13}{62}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B13%7D%7B62%7D)
We should fuigre it out by first doing 1.7x since we don't know the 2 different widths and lengths.
P= 2*length + 2*width(the distance around)
Question says...
2(1.7x)+2x = 28
3.4x+2x=28
5.4x=28
X= 28m divided by 5.4
x = 5.2m: the width The length is : 8.8m
Answer:
The answer is (h).
Step-by-step explanation:
When y = 2^x is shifted 4 units left, the x shifts 4 units to the left and x becomes (x+4). When the graph is shifted to units down, y has to be subtracted by 2.
The function becomes
y = 2^(x+4) -2.
Finally, you shift -2 to the same side as y.
This becomes
y+2 = 2^(x+4) which is (h)
Answer:
The area of circular plate is <u>144π square centimeters</u>.
Step-by-step explanation :
<h3><u>Solution</u> :</h3>
Here, we have given that the radius of circular plate is 12 centimeters.
So, finding the area of circular plate by substituting the values in the formula :
![\longrightarrow{\pmb{\sf{Area_{(Circle)} = \pi{r}^{2}}}}](https://tex.z-dn.net/?f=%5Clongrightarrow%7B%5Cpmb%7B%5Csf%7BArea_%7B%28Circle%29%7D%20%3D%20%5Cpi%7Br%7D%5E%7B2%7D%7D%7D%7D)
![\longrightarrow{\sf{Area_{(Circle)} = \pi{(12)}^{2}}}](https://tex.z-dn.net/?f=%5Clongrightarrow%7B%5Csf%7BArea_%7B%28Circle%29%7D%20%3D%20%5Cpi%7B%2812%29%7D%5E%7B2%7D%7D%7D)
![\longrightarrow{\sf{Area_{(Circle)} = \pi{(12 \times 12)}}}](https://tex.z-dn.net/?f=%5Clongrightarrow%7B%5Csf%7BArea_%7B%28Circle%29%7D%20%3D%20%5Cpi%7B%2812%20%5Ctimes%2012%29%7D%7D%7D)
![\longrightarrow{\sf{Area_{(Circle)} = \pi{(144)}}}](https://tex.z-dn.net/?f=%5Clongrightarrow%7B%5Csf%7BArea_%7B%28Circle%29%7D%20%3D%20%5Cpi%7B%28144%29%7D%7D%7D)
![\longrightarrow{\sf{Area_{(Circle)} = \pi \times 144}}](https://tex.z-dn.net/?f=%5Clongrightarrow%7B%5Csf%7BArea_%7B%28Circle%29%7D%20%3D%20%5Cpi%20%5Ctimes%20144%7D%7D)
![\longrightarrow{\sf{Area_{(Circle)} = 144\pi}}](https://tex.z-dn.net/?f=%5Clongrightarrow%7B%5Csf%7BArea_%7B%28Circle%29%7D%20%3D%20144%5Cpi%7D%7D)
![\star{\underline{\boxed{\frak{\purple{Area_{(Circle)} = 144\pi\: {cm}^{2}}}}}}](https://tex.z-dn.net/?f=%5Cstar%7B%5Cunderline%7B%5Cboxed%7B%5Cfrak%7B%5Cpurple%7BArea_%7B%28Circle%29%7D%20%3D%20144%5Cpi%5C%3A%20%20%7Bcm%7D%5E%7B2%7D%7D%7D%7D%7D%7D)
Hence, the area of circular plate is 144π square centimeters.
![\rule{300}{2.5}](https://tex.z-dn.net/?f=%5Crule%7B300%7D%7B2.5%7D)
Answer:
32.5 ft^2
Step-by-step explanation:
All sides of a square have the same length. Area would therefore be:
(5.7 ft)(5.7 ft) = 32.5 ft^2